Proton exchange membrane, preparation method and application thereof
By introducing sulfonated polyaryletherketone sulfone with nitrogen-containing heterocycle side chains into the proton exchange membrane and doping them with phosphoric acid, the problem of water loss in the existing proton exchange membrane at high temperature is solved, and high proton conduction ability and durability at high temperature is achieved.
Patent Information
- Application Number
- CN202411974342.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-04
AI Technical Summary
The existing proton exchange membrane loses water under high temperature conditions, and the proton conduction ability decreases, making it impossible to take into account the problems of high temperature and high conductivity.
The sulfonated polyaryletherketone sulfone with nitrogen-containing heterocyclic side chain is used and phosphoric acid doped. Through the acid-base interaction of heterocyclic nitrogen and phosphoric acid, the proton conduction ability is maintained and the loss of phosphoric acid is slowed.
The proton exchange membrane has achieved high proton conduction capability under high temperature and anhydrous conditions, overcomes the temperature limitations of traditional fuel cell proton exchange membranes, and has the characteristics of high conductivity, high temperature resistance and high durability.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of functional polymer materials, and in particular to a proton exchange membrane, a preparation method and application thereof. Background Art
[0002] Proton exchange membrane fuel cells (PEMFC) convert the chemical energy of hydrogen directly into electrical energy through electrochemical reactions. The reaction products are mainly water and carbon dioxide. It is a new type of renewable, environmentally friendly clean energy device. Fuel cells are not limited by the Carnot cycle and can achieve an energy conversion efficiency of 45-60%.
[0003] As one of the core components of fuel cells, the proton exchange membrane plays a role in isolating the positive and negative electrodes and conducting the product (proton) of the anode hydrogen oxidation reaction (HOR) to the cathode to participate in the oxygen reduction reaction (ORR). At present, the most mature and widely used proton exchange membrane is the perfluorosulfonic acid (PFSA) proton exchange membrane. Since its proton conduction depends on the water content in the membrane, the optimal operating temperature is generally 80-90°C. When the operating temperature is too high, the perfluorosulfonic acid membrane will lose water significantly, and the proton conduction capacity will drop sharply, limiting the application of fuel cells. Therefore, the development of high temperature resistant proton exchange membrane (HTPEM) is one of the research hotspots in the field of fuel cells. Its advantages are: (1) high temperature conditions are conducive to higher kinetic efficiency of electrochemical reactions, thereby improving fuel utilization and battery output power; (2) high temperature conditions can inhibit the adsorption of CO on the catalyst and weaken the poisoning effect of CO on the catalyst; (3) high temperature working conditions can effectively reduce the risk of water flooding inside the fuel cell, which is conducive to providing easier water and heat management for the battery system.
[0004] Chinese application CN201810286112.6 is a high-temperature proton exchange membrane and its preparation method, which discloses a preparation method based on bis(hydroxyethyl)sulfone-4,5-dicarboxyimidazole condensation polymer, and further doping metal organic framework and phosphoric acid on the basis of the condensation polymer to prepare a high-temperature proton exchange membrane. However, this technical solution has the following disadvantages: (1) The NH bond on the imidazole group is relatively active and prone to oxidative degradation. The methods to solve this problem (cross-linking, end group or side chain modification, doping with free radical scavengers and surface modification, etc.) often cause a decrease in proton conductivity or have limited improvement effects. (2) The reaction conditions of imidazole polymers are harsh during the synthesis process, and the preparation process is difficult. Although the production cost is lower than that of perfluoroproton exchange membranes, it is higher than that of poly(aryl ether sulfone) materials, and its industrial production needs further research. Chinese application CN201310694575.3 is a high-temperature polyimide proton exchange membrane and its preparation method, which discloses that a nitrogen-containing heterocyclic sulfonated polyimide polymer is obtained by copolymerizing a dianhydride monomer, a sulfonated diamine monomer, and a nitrogen-containing heterocyclic diamine monomer, and then phosphoric acid is doped after solidification to prepare a high-temperature polyimide proton exchange membrane. However, the proton conductivity of the proton exchange membrane prepared by this technical solution is 10 at 120°C. -6 ~10 -3 S / cm, the conductivity is too low, and this level of conductivity is basically meaningless. Summary of the invention
[0005] The main purpose of the present invention is to provide a proton exchange membrane, a preparation method and application thereof, so as to solve the problem that the proton exchange membrane in the prior art cannot have both high temperature resistance and high conductivity.
[0006] In order to achieve the above object, according to one aspect of the present invention, a proton exchange membrane is provided, wherein the proton exchange membrane is doped with phosphoric acid, and the membrane material comprises a sulfonated polyaryletherketonesulfone containing a nitrogen heterocyclic side chain, and the sulfonated polyaryletherketonesulfone containing a nitrogen heterocyclic side chain has a structure shown in the general formula (I):
[0007]
[0008] The number average molecular weight of the sulfonated polyaryletherketonesulfone containing a nitrogen heterocyclic side chain is 10,000 to 300,000, 0% < x < 100%, 0% < y < 100%, 0% ≤ z < 100%, and x + y + z = 100%;
[0009] R has the structure shown in general formula (II):
[0010]
[0011] Among them, R1 is selected from imidazole or pyrazolyl, R2 is a branched or branched alkyl of C1 to C4, a is 1 or 2; Ar0 is a first non-sulfonated aromatic monomer, Ar1 is a sulfonated aromatic monomer, and Ar2 is a second non-sulfonated aromatic monomer.
[0012] Furthermore, Ar0 has a structure shown in general formula (III):
[0013]
[0014] Wherein, A is selected from a vacant bond, O, a carbonyl group, or phenylene; and / or
[0015] Ar1 has a structure shown in general formula (IV):
[0016]
[0017] Wherein, B is selected from a vacant bond, O, a carbonyl group, or phenylene; and / or
[0018] Ar2 has the structure shown in general formula (V):
[0019]
[0020] Wherein, C is selected from a vacant bond, O, a carbonyl group or Furthermore, R has any one of the following structures:
[0021] Further, the sulfonated polyaryletherketonesulfone containing a nitrogen heterocyclic side chain has any one of the following structures:
[0022]
[0023]
[0024] The number average molecular weight of the sulfonated polyaryletherketonesulfone containing a nitrogen heterocyclic side chain is 18000-23000, 0%<x<100%, 0%<y<100%, 0%≤z<100%, and x+y+z=100%.
[0025] Furthermore, the doping amount of phosphoric acid in the proton exchange membrane is 10-50% by weight; and / or the thickness of the proton exchange membrane is 10-100 μm.
[0026] According to another aspect of the present invention, a method for preparing the above-mentioned proton exchange membrane of the present invention is provided, comprising the following steps: step S1, adding a nitrogen heterocyclic monomer raw material, a sulfonated aromatic monomer raw material, a first non-sulfonated aromatic monomer raw material and a second non-sulfonated aromatic monomer raw material in a reaction container in sequence to obtain a mixed raw material, and then adding potassium carbonate, an organic solvent and toluene to obtain a raw material solution; step S2, heating the raw material solution under nitrogen protection to obtain a polymerization system solution; step S3, adding the polymerization system solution to a precipitant to precipitate a polymer to obtain a sulfonated polyaryletherketonesulfone containing a nitrogen heterocyclic side chain; step S4, dissolving the sulfonated polyaryletherketonesulfone containing a nitrogen heterocyclic side chain with dimethyl sulfoxide, and preparing it into a thin film by casting, spraying or spin coating; step S5, soaking the thin film in an ethanol solution of phosphoric acid, and drying it to obtain a proton exchange membrane.
[0027] Further, the molar ratio of the nitrogen heterocyclic monomer raw material, the sulfonated aromatic hydrocarbon monomer raw material, the second non-sulfonated aromatic hydrocarbon monomer raw material and the first non-sulfonated aromatic hydrocarbon monomer raw material is (1-2):1:(0-1):3; and / or the nitrogen heterocyclic monomer raw material includes one or more of the following substances: 2,3,5,6-tetrafluoroterephthalide [(3-pyrazole)benzoyl], 2,3,5,6-tetrafluoroterephthalide [(3-imidazole)benzoyl], 2,3,5,6-tetrafluoroterephthalide [(3-methyl-5-imidazole)benzoyl], 2,3,5,6-tetrafluoroterephthalide [(4-methyl-5-imidazole)benzoyl]; and / or the sulfonated aromatic hydrocarbon monomer raw material includes the following One or more substances: 3,3'-disulfonate-4,4'-difluorobenzophenone disodium salt, 3,3'-disulfonate-4,4'-difluorodiphenyl sulfone disodium salt; and / or the first non-sulfonated aromatic monomer raw material includes one or more of the following substances: 4,4'-dihydroxybiphenyl, 4,4'-dihydroxydiphenyl ether, 4,4'-dihydroxybenzophenone, 4,4'-dihydroxydiphenyl sulfone, bisphenol A, bisphenol AF; and / or the second non-sulfonated aromatic monomer raw material includes one or more of the following substances: 4,4'-difluorobiphenyl, 4,4'-difluorodiphenyl ether, 4,4'-difluorobenzophenone, 4,4'-difluorodiphenyl sulfone.
[0028] Furthermore, the molar ratio of the mixed raw material to potassium carbonate is 1:(1.0-1.1); and / or the organic solvent includes N,N-dimethylacetamide and / or N-methylpyrrolidone; and / or in the raw material solution, the mass concentration of the mixed raw material is 8-35%.
[0029] Furthermore, the heating includes a first heating and a second heating performed sequentially, the first heating temperature is 110-130°C, the time is 5-7h, the second heating temperature is 150-170°C, the time is 28-32h; and / or the precipitant is an acetic acid aqueous solution with a mass concentration of 40-80%; and / or the mass concentration of the ethanol solution of phosphoric acid is 40-80%; and / or the soaking temperature is 40-80°C, and the time is 24-48h.
[0030] According to another aspect of the present invention, a fuel cell is provided, comprising the above-mentioned proton exchange membrane of the present invention.
[0031] By applying the technical solution of the present invention, a nitrogen heterocyclic structure is introduced into the side chain of the sulfonated polyaryletherketonesulfone, and phosphoric acid is doped, so that the proton exchange membrane can maintain its proton conduction ability under high-temperature anhydrous conditions by virtue of the self-ionization characteristics of phosphoric acid, thereby realizing a high-temperature working scenario of the fuel cell. Moreover, the acid-base interaction between heterocyclic nitrogen and phosphoric acid is beneficial to slowing down the loss of phosphoric acid when the fuel cell is running at high temperature, thereby increasing the service life of the proton exchange membrane. The proton exchange membrane of the present invention can overcome the operating temperature limit of no more than 90°C for the perfluorosulfonic acid proton exchange membrane used in traditional fuel cells, and has the characteristics of high conductivity, high temperature resistance, and high durability. DETAILED DESCRIPTION
[0032] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0033] It should be noted that “*” in the structural formula of the present invention refers to the connection site of the group.
[0034] As described in the background of the present invention, there is a problem in the prior art that proton exchange membranes cannot take into account both high temperature resistance and high conductivity. In order to solve the above problem, in a typical embodiment of the present invention, a proton exchange membrane is provided, the proton exchange membrane is doped with phosphoric acid, and the membrane material includes a sulfonated polyaryletherketonesulfone containing a nitrogen heterocyclic side chain, and the sulfonated polyaryletherketonesulfone containing a nitrogen heterocyclic side chain has a structure shown in the general formula (I):
[0035]
[0036] The number average molecular weight of the sulfonated polyaryletherketonesulfone containing a nitrogen heterocyclic side chain is 10,000 to 300,000, 0% < x < 100%, 0% < y < 100%, 0% ≤ z < 100%, and x + y + z = 100%; R has a structure shown in the general formula (II):
[0037]
[0038] Wherein, R1 is selected from imidazole or pyrazolyl, R2 is a C1-C4 branched or branched alkyl, a is 1 or 2; Ar0 is a first non-sulfonated aromatic monomer, Ar1 is a sulfonated aromatic monomer, and Ar2 is a second non-sulfonated aromatic monomer. Wherein, x, y and z are the molar percentages of different repeating units in the entire polymer.
[0039] The proton exchange membrane of the present invention comprises a nitrogen heterocyclic structural unit (a unit defined by x), a sulfonated structural unit (a unit defined by y) and an optional non-sulfonated structural unit (a unit defined by z), and the sulfonated site is precisely controllable. The sulfonated structural unit is used to provide a proton conduction site to ensure the conduction capacity of the proton exchange membrane at low temperatures, and to coordinate with the doped phosphoric acid to conduct protons at high temperatures, and the non-sulfonated structural unit is used to adjust the ion exchange capacity of the polymer, achieve the hydrophilic / hydrophobic balance of the polymer, and simultaneously increase the mechanical strength of the polymer, thereby improving the physical stability of the proton exchange membrane at high temperatures.
[0040] The present invention introduces a nitrogen heterocyclic structure into the side chain of the sulfonated polyaryletherketonesulfone and performs phosphoric acid doping, so that the proton exchange membrane can maintain its proton conduction ability under high-temperature anhydrous conditions by virtue of the self-ionization characteristics of phosphoric acid, thereby realizing a high-temperature working scenario of the fuel cell. Moreover, the acid-base interaction between heterocyclic nitrogen and phosphoric acid helps to slow down the loss of phosphoric acid when the fuel cell is running at high temperature, thereby increasing the service life of the proton exchange membrane. The proton exchange membrane of the present invention can overcome the operating temperature limit of no more than 90°C for the perfluorosulfonic acid proton exchange membrane used in traditional fuel cells, and has the characteristics of high conductivity, high temperature resistance, and high durability.
[0041] In a preferred embodiment, Ar0 has a structure shown in general formula (III):
[0042]
[0043] Wherein, A is selected from a vacant bond, O, a carbonyl group, or phenylene; and / or
[0044] Ar1 has a structure shown in general formula (IV):
[0045]
[0046] Wherein, B is selected from a vacant bond, O, a carbonyl group, or phenylene; and / or
[0047] Ar2 has the structure shown in general formula (V):
[0048]
[0049] Wherein, C is selected from a vacant bond, O, a carbonyl group or
[0050] The above-mentioned non-sulfonated aromatic monomer Ar0 can further enhance the thermal stability of the polymer, so that the proton exchange membrane can maintain structural integrity at high temperatures, which is conducive to further improving the high temperature resistance of the proton exchange membrane by cooperating with heterocyclic nitrogen and phosphoric acid. The sulfonic acid group introduced by the sulfonated aromatic monomer is an active site for proton conduction. The above-mentioned sulfonated aromatic monomer Ar1 can further improve the conductivity of the proton exchange membrane, which is conducive to cooperating with heterocyclic nitrogen and phosphoric acid so that the proton exchange membrane can retain moisture at high temperatures to better maintain the proton transfer path. The above-mentioned non-sulfonated aromatic monomer Ar2 can further optimize the water distribution in the membrane by regulating the hydrophilic / hydrophobic balance of the polymer, while increasing the mechanical strength of the polymer, which is conducive to cooperating with heterocyclic nitrogen and phosphoric acid to better improve the physical stability of the proton exchange membrane at high temperatures.
[0051] In order to better slow down the loss of phosphoric acid when the fuel cell is running at high temperature, thereby further improving the service life of the proton exchange membrane, in a preferred embodiment, R has any one of the following structures:
[0052] In a preferred embodiment, the sulfonated polyaryletherketonesulfone containing a nitrogen heterocyclic side chain has any one of the following structures:
[0053]
[0054]
[0055] The number average molecular weight of the sulfonated polyaryletherketonesulfone containing a nitrogen heterocyclic side chain is 18000-23000, 0%<x<100%, 0%<y<100%, 0%≤z<100%, and x+y+z=100%. Under the above conditions, the proton exchange membrane has higher conductivity, better high temperature resistance and longer service life.
[0056] In a preferred embodiment, the doping amount of phosphoric acid in the proton exchange membrane is 10-50% by weight; and / or the thickness of the proton exchange membrane is 10-100 μm. The appropriate amount of phosphoric acid doping can further improve the proton conductivity of the membrane and cooperate with the nitrogen heterocycle to improve the conductivity of the proton exchange membrane under high temperature conditions. The appropriate phosphoric acid doping amount and membrane thickness are more conducive to further optimizing the conductivity of the proton exchange membrane at high temperature without sacrificing the durability and mechanical properties of the membrane.
[0057] In another typical embodiment of the present invention, a method for preparing the above-mentioned proton exchange membrane of the present invention is also provided, comprising the following steps: step S1, adding a nitrogen heterocyclic monomer raw material, a sulfonated aromatic monomer raw material, a first non-sulfonated aromatic monomer raw material and a second non-sulfonated aromatic monomer raw material in a reaction container in sequence to obtain a mixed raw material, and then adding potassium carbonate, an organic solvent and toluene to obtain a raw material solution; step S2, heating the raw material solution under nitrogen protection to obtain a polymerization system solution; step S3, adding the polymerization system solution to a precipitant to precipitate a polymer to obtain a sulfonated polyaryletherketonesulfone containing a nitrogen heterocyclic side chain; step S4, dissolving the sulfonated polyaryletherketonesulfone containing a nitrogen heterocyclic side chain with dimethyl sulfoxide, and preparing it into a thin film by casting, spraying or spin coating; step S5, soaking the thin film in an ethanol solution of phosphoric acid and drying it to obtain a proton exchange membrane.
[0058] Specifically, the present invention first adds nitrogen heterocyclic monomer raw material, sulfonated aromatic monomer raw material, first non-sulfonated aromatic monomer raw material and second non-sulfonated aromatic monomer raw material in a reaction vessel in sequence to obtain a mixed raw material, then adds potassium carbonate, organic solvent and toluene to obtain a raw material solution, and heats it under nitrogen protection to obtain a viscous polymerization system solution, wherein potassium carbonate is used as a catalyst and toluene is added as a water-carrying agent in an appropriate amount. In this process, a polymer is obtained by a nucleophilic substitution chain reaction between a hydroxyl group and fluorine. Then the polymerization system solution is added to a precipitant, and the polymer is insoluble in the precipitant and precipitates, while removing the organic solvent and potassium carbonate dissolved in the precipitant in the reaction system, repeatedly washing with water and drying to obtain a sulfonated polyaryletherketonesulfone containing a nitrogen heterocyclic side chain; finally, the sulfonated polyaryletherketonesulfone containing a nitrogen heterocyclic side chain is dissolved with dimethyl sulfoxide, and a film is prepared by casting, spraying or spin coating, and soaked in an ethanol solution of phosphoric acid, and dried to obtain a phosphoric acid-doped proton exchange membrane. The preparation method of the present invention is simple and easy to operate. The prepared proton exchange membrane can overcome the operating temperature limit of no more than 90° C. of the perfluorosulfonic acid proton exchange membrane used in traditional fuel cells, and has the characteristics of high conductivity, high temperature resistance and high durability.
[0059] Optimized monomer molar ratio and monomer selection have an improving effect on the proton exchange membrane's ability to balance high temperature resistance and high conductivity. In a preferred embodiment, the molar ratio of the nitrogen heterocyclic monomer raw material, the sulfonated aromatic monomer raw material, the second non-sulfonated aromatic monomer raw material and the first non-sulfonated aromatic monomer raw material is (1-2):1:(0-1):3; and / or the nitrogen heterocyclic monomer raw material includes one or more of the following substances: 2,3,5,6-tetrafluoroterephthalide [(3-pyrazole)benzoyl], 2,3,5,6-tetrafluoroterephthalide [(3-imidazole)benzoyl], 2,3,5,6-tetrafluoroterephthalide [(3-methyl-5-imidazole)benzoyl], 2,3,5,6-tetrafluoroterephthalide [(4-methyl-5-imidazole)benzoyl]; and / or sulfonated aromatic monomer raw material The invention comprises one or more of the following substances: 3,3'-disulfonate-4,4'-difluorobenzophenone disodium salt, 3,3'-disulfonate-4,4'-difluorodiphenyl sulfone disodium salt; and / or the first non-sulfonated aromatic monomer raw material comprises one or more of the following substances: 4,4'-dihydroxybiphenyl, 4,4'-dihydroxydiphenyl ether, 4,4'-dihydroxybenzophenone, 4,4'-dihydroxydiphenyl sulfone, bisphenol A, bisphenol AF; and / or the second non-sulfonated aromatic monomer raw material comprises one or more of the following substances: 4,4'-difluorobiphenyl, 4,4'-difluorodiphenyl ether, 4,4'-difluorobenzophenone, 4,4'-difluorodiphenyl sulfone.
[0060] The above-mentioned nitrogen heterocyclic monomer raw materials can further increase the high temperature stability of the proton exchange membrane, and its heterocyclic structure is more conducive to interacting with phosphoric acid, slowing down the loss of phosphoric acid, and maintaining the conductivity of the proton exchange membrane at high temperatures. The above-mentioned sulfonated aromatic monomer raw materials are conducive to providing more suitable sulfonic acid groups as the key to proton conduction, ensuring that the proton exchange membrane can maintain high conductivity even at high temperatures. The above-mentioned non-sulfonated aromatic monomer raw materials can further regulate the hydrophilicity of the proton exchange membrane, prevent excessive water loss, and enhance the mechanical properties of the proton exchange membrane. When the molar ratio of the monomer raw materials is within the above range, the conductivity and thermal stability of the proton exchange membrane can be better balanced, and it is also conducive to the precise control of the side chain sulfonation sites.
[0061] In order to further improve the efficiency of the copolymerization reaction, maintain the high conductivity of the proton exchange membrane, and reduce the negative impact of excess alkali on the stability of the membrane structure, so as to improve the high temperature resistance of the proton exchange membrane, in a preferred embodiment, the molar ratio of the mixed raw material to potassium carbonate is 1: (1.0-1.1); and / or the organic solvent includes N, N-dimethylacetamide and / or N-methylpyrrolidone; and / or in the raw material solution, the mass concentration of the mixed raw material is 8-35%. The above-mentioned organic solvent has high solubility and thermal stability, which can further promote the uniform dispersion and polymerization reaction of the monomer, form a copolymer with uniform structure and stable performance, and then prepare a proton exchange membrane with better high temperature stability. The mass concentration of the mixed raw material in the raw material solution is controlled within the above range, so that the reaction system has a suitable viscosity, which is conducive to the formation of a continuous and uniform proton exchange membrane structure, and at the same time ensures sufficient sulfonation sites to maintain the proton conductivity of the proton exchange membrane at high temperature, so as to achieve a balance between high conductivity and high temperature resistance.
[0062] The optimized heating step can effectively promote the polymerization reaction of the monomers to form a polymer with a better cross-linking degree and a stable structure, which can not only enhance the thermal stability of the membrane so that it can withstand high temperature environments, but also optimize the proton conduction path of the membrane, which helps to maintain high conductivity at high temperatures. In a preferred embodiment, the heating includes a first heating and a second heating performed in sequence, the temperature of the first heating is 110-130°C, the time is 5-7h, the temperature of the second heating is 150-170°C, the time is 28-32h; and / or the precipitant is an acetic acid aqueous solution with a mass concentration of 40-80%; and / or the mass concentration of the ethanol solution of phosphoric acid is 40-80%; and / or the soaking temperature is 40-80°C, and the time is 24-48h. The above-mentioned precipitant can more effectively control the precipitation rate and morphology of the polymer, ensure the uniformity and structural integrity of the membrane, and further improve the high temperature resistance of the membrane. Under the above-mentioned soaking conditions, phosphoric acid can be more fully infiltrated into the membrane to form a stable acid-base environment, which can maintain proton conduction even in high temperature and low water environments, and significantly improve the conductivity of the membrane.
[0063] In another typical embodiment of the present invention, a fuel cell is provided, comprising the proton exchange membrane of the present invention. Since the proton exchange membrane of the present invention is used as a key component, the fuel cell has a significantly improved service life.
[0064] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0065] Example 1
[0066] Step S1, in a 100 mL three-necked flask equipped with a magnetic stirrer, a water separator, a condenser and a gas guide tube, 6 mmol of 2,3,5,6-tetrafluoroterephthalide [(3-pyrazole)benzoyl], 6 mmol of 3,3'-disulfonic acid-4,4'-difluorobenzophenone disodium salt, 6 mmol of 4,4'-difluorodiphenyl ether and 18 mmol of 4,4'-dihydroxybenzophenone are added in a molar ratio of 1:1:1:3 to obtain a mixed raw material, and then 36 mmol of potassium carbonate in an amount equal to the molar amount of the mixed raw material, as well as 40 mL of DMAc and 10 mL of toluene are added to obtain a raw material solution, wherein the mass concentration of the mixed raw material is 17%.
[0067] Step S2, under nitrogen protection, the raw material solution is heated to 120°C, and the timing starts at 6 hours when liquid drops begin to drip in the condenser, and then the system is heated to 160°C for 30 hours to obtain a viscous polymerization system solution.
[0068] Step S3, pouring the polymerization system solution into an acetic acid aqueous solution with a mass concentration of 50% to precipitate a polymer, repeatedly washing with water and then drying to obtain a sulfonated polyaryletherketonesulfone containing a nitrogen heterocyclic side chain.
[0069] Step S4, dissolving the sulfonated polyaryletherketonesulfone having a nitrogen-containing heterocyclic side chain in dimethyl sulfoxide, and preparing a film by a casting method.
[0070] Step S5, soak the film in an ethanol solution of 60% phosphoric acid at 60°C for 36 hours, wipe off excess phosphoric acid on the surface of the film with a dust-free cloth, and dry it in a 60°C forced air oven for 8 hours to obtain a proton exchange membrane with a phosphoric acid doping amount of 20%.
[0071] The sulfonated polyaryletherketonesulfone having a nitrogen-containing heterocyclic side chain has the following structure, and x+y+z=100%, x:y:z=1:1:1.
[0072]
[0073] Example 2
[0074] Step S1, in a 100mL three-necked flask equipped with a magnetic stirrer, a water separator, a condenser and an air guide tube, 6mmol of 2,3,5,6-tetrafluoroterephthaloyl[(3-imidazole)benzoyl], 6mmol of 3,3'-disulfonic acid-4,4'-difluorodiphenyl sulfone disodium salt, 6mmol of 4,4'-difluorodiphenyl sulfone and 18mmol of 4,4'-dihydroxydiphenyl ether are added in a molar ratio of 1:1:1:3 to obtain a mixed raw material, and then 36mmol of potassium carbonate in an amount equal to the molar amount of the above mixed raw material, as well as 40mL of DMAc and 10mL of toluene are added to obtain a raw material solution, wherein the mass concentration of the mixed raw material is 17%.
[0075] Step S2, under nitrogen protection, the raw material solution is heated to 120°C, and the timing starts at 6 hours when liquid drops begin to drip in the condenser, and then the system is heated to 160°C for 30 hours to obtain a viscous polymerization system solution.
[0076] Step S3, pouring the polymerization system solution into an acetic acid aqueous solution with a mass concentration of 50% to precipitate a polymer, repeatedly washing with water and then drying to obtain a sulfonated polyaryletherketonesulfone containing a nitrogen heterocyclic side chain.
[0077] Step S4, dissolving the sulfonated polyaryletherketonesulfone having a nitrogen-containing heterocyclic side chain in dimethyl sulfoxide, and preparing a film by a casting method.
[0078] Step S5, soak the film in an ethanol solution of 60% phosphoric acid at 60°C for 36 hours, wipe off excess phosphoric acid on the membrane surface with a dust-free cloth, and dry it in a 60°C forced air oven for 8 hours to obtain a proton exchange membrane with a phosphoric acid doping level of 21%.
[0079] The sulfonated polyaryletherketonesulfone having a nitrogen-containing heterocyclic side chain has the following structure, and x+y+z=100%, x:y:z=1:1:1.
[0080]
[0081] Example 3
[0082] Step S1, in a 100 mL three-necked flask equipped with a magnetic stirrer, a water separator, a condenser and an air guide tube, 6 mmol of 2,3,5,6-tetrafluoroterephthaloyl[(3-methyl-5-imidazole)benzoyl], 6 mmol of 3,3'-disulfonic acid-4,4'-difluorodiphenyl sulfone disodium salt, 6 mmol of 4,4'-difluorodiphenyl sulfone and 18 mmol of bisphenol A are added in sequence in a molar ratio of 1:1:1:3 to obtain a mixed raw material, and then 36 mmol of potassium carbonate in an amount equimolar to the above-mentioned mixed raw material, as well as 40 mL of DMAc and 10 mL of toluene are added to obtain a raw material solution, wherein the mass concentration of the mixed raw material is 18%.
[0083] Step S2, under nitrogen protection, the raw material solution is heated to 120°C, and the timing starts at 6 hours when liquid drops begin to drip in the condenser, and then the system is heated to 160°C for 30 hours to obtain a viscous polymerization system solution.
[0084] Step S3, pouring the polymerization system solution into an acetic acid aqueous solution with a mass concentration of 50% to precipitate a polymer, repeatedly washing with water and then drying to obtain a sulfonated polyaryletherketonesulfone containing a nitrogen heterocyclic side chain.
[0085] Step S4, dissolving the sulfonated polyaryletherketonesulfone having a nitrogen-containing heterocyclic side chain in dimethyl sulfoxide, and preparing a film by a casting method.
[0086] Step S5, soak the film in an ethanol solution of 60% phosphoric acid at 60°C for 36 hours, wipe off excess phosphoric acid on the membrane surface with a dust-free cloth, and dry it in a 60°C forced air oven for 8 hours to obtain a proton exchange membrane with a phosphoric acid doping level of 19%.
[0087] The sulfonated polyaryletherketonesulfone having a nitrogen-containing heterocyclic side chain has the following structure, and x+y+z=100%, x:y:z=1:1:1.
[0088]
[0089] Example 4
[0090] Step S1, in a 100 mL three-necked flask equipped with a magnetic stirrer, a water separator, a condenser and an air guide tube, 12 mmol of 2,3,5,6-tetrafluoroterephthaloyl[(3-imidazole)benzoyl], 6 mmol of 3,3'-disulfonic acid-4,4'-difluorodiphenylsulfone disodium salt and 18 mmol of 4,4'-dihydroxybiphenyl are added in a molar ratio of 2:1:3 to obtain a mixed raw material, and then 36 mmol of potassium carbonate in an amount equal to the molar amount of the mixed raw material, as well as 40 mL of DMAc and 10 mL of toluene are added to obtain a raw material solution, wherein the mass concentration of the mixed raw material is 19%.
[0091] Step S2, under nitrogen protection, the raw material solution is heated to 120°C, and the timing starts at 6 hours when liquid drops begin to drip in the condenser, and then the system is heated to 160°C for 30 hours to obtain a viscous polymerization system solution.
[0092] Step S3, pouring the polymerization system solution into an acetic acid aqueous solution with a mass concentration of 50% to precipitate a polymer, repeatedly washing with water and then drying to obtain a sulfonated polyaryletherketonesulfone containing a nitrogen heterocyclic side chain.
[0093] Step S4, dissolving the sulfonated polyaryletherketonesulfone having a nitrogen-containing heterocyclic side chain in dimethyl sulfoxide, and preparing a film by a casting method.
[0094] Step S5, soak the film in an ethanol solution of 60% phosphoric acid at 60°C for 36 hours, wipe off excess phosphoric acid on the surface of the film with a dust-free cloth, and dry it in a 60°C forced air oven for 8 hours to obtain a proton exchange membrane with a phosphoric acid doping level of 28%.
[0095] The sulfonated polyaryletherketonesulfone having a nitrogen-containing heterocyclic side chain has the following structure, and x+y=100%, and x:y=2:1.
[0096]
[0097] Example 5
[0098] The difference from Example 1 is that, in step S1, in a 100 mL three-necked flask equipped with a magnetic stirrer, a water separator, a condenser and an air guide tube, 3 mmol of 2,3,5,6-tetrafluoroterephthalide [(3-pyrazole)benzoyl], 3 mmol of 3,3'-disulfonic acid-4,4'-difluorobenzophenone disodium salt, 3 mmol of 4,4'-difluorodiphenyl ether and 9 mmol of 4,4'-dihydroxybenzophenone are added in a molar ratio of 1:1:1:3 to obtain a mixed raw material, and then potassium carbonate (with a molar ratio of 1:1.0 to the above mixed raw material) is added, as well as 50 mL of DMAc and 10 mL of toluene to obtain a raw material solution, wherein the mass concentration of the mixed raw material is 8%.
[0099] Among them, in the sulfonated polyaryletherketonesulfone containing a nitrogen heterocyclic side chain, x+y+z=100%, x:y:z=1:1:1.
[0100] Example 6
[0101] The difference from Example 1 is that, in step S1, in a 100 mL three-necked flask equipped with a magnetic stirrer, a water separator, a condenser and an air guide tube, 6 mmol of 2,3,5,6-tetrafluoroterephthalide [(3-pyrazole)benzoyl], 6 mmol of 3,3'-disulfonic acid-4,4'-difluorobenzophenone disodium salt, 6 mmol of 4,4'-difluorodiphenyl ether and 18 mmol of 4,4'-dihydroxybenzophenone are added in a molar ratio of 1:1:1:3 to obtain a mixed raw material, and then potassium carbonate (with a molar ratio of 1:1.1 to the above-mentioned mixed raw material) is added, as well as 16 mL of DMAc and 5 mL of toluene to obtain a raw material solution, wherein the mass concentration of the mixed raw material is 33%.
[0102] Among them, in the sulfonated polyaryletherketonesulfone containing a nitrogen heterocyclic side chain, x+y+z=100%, x:y:z=1:1:1.
[0103] Example 7
[0104] The difference from Example 1 is that
[0105] Step S2, under nitrogen protection, the raw material solution is heated to 110°C, and the timing starts at 7h when liquid drops begin to drip in the condenser, and then the system is heated to 150°C for reaction for 32h to obtain a viscous polymerization system solution.
[0106] Step S3, pouring the polymerization system solution into an acetic acid aqueous solution with a mass concentration of 40% to precipitate a polymer, repeatedly washing with water and then drying to obtain a sulfonated polyaryletherketonesulfone containing a nitrogen heterocyclic side chain.
[0107] Example 8
[0108] The difference from Example 1 is that
[0109] Step S2, under nitrogen protection, the raw material solution is heated to 130°C, and the timing of 5 hours begins when liquid drops begin to drip from the condenser, and then the system is heated to 170°C for 28 hours to obtain a viscous polymerization system solution.
[0110] Step S3, pouring the polymerization system solution into an acetic acid aqueous solution with a mass concentration of 80% to precipitate a polymer, repeatedly washing with water and then drying to obtain a sulfonated polyaryletherketonesulfone containing a nitrogen heterocyclic side chain.
[0111] Example 9
[0112] The difference from Example 1 is that
[0113] Step S4, dissolving the sulfonated polyaryletherketonesulfone having a nitrogen-containing heterocyclic side chain in dimethyl sulfoxide, and preparing a film by a casting method.
[0114] Step S5, soak the film in an ethanol solution of phosphoric acid with a mass concentration of 40% at 40°C for 48 hours, wipe off excess phosphoric acid on the surface of the membrane with a dust-free cloth, and place it in a 60°C forced air oven for drying for 8 hours to obtain a proton exchange membrane with a phosphoric acid doping amount of 16%.
[0115] Example 10
[0116] The difference from Example 1 is that
[0117] Step S4, dissolving the sulfonated polyaryletherketonesulfone having a nitrogen-containing heterocyclic side chain in dimethyl sulfoxide, and preparing a film by a casting method.
[0118] Step S5, soak the film in an ethanol solution of phosphoric acid with a mass concentration of 80% at 80°C for 24 hours, wipe off excess phosphoric acid on the surface of the membrane with a dust-free cloth, and place it in a 60°C forced air oven for drying for 8 hours to obtain a proton exchange membrane with a phosphoric acid doping amount of 28%.
[0119] Comparative Example 1
[0120] Commercially available Nafion 212 membrane.
[0121] The performance of the proton exchange membranes prepared in the above examples and comparative examples was tested, and the results are shown in Table 1.
[0122] Test method:
[0123] Number average molecular weight of copolymer: the polymer was dissolved in anhydrous N,N-dimethylformamide (DMF) with a polymer concentration of 2 mg / ml, and the number average molecular weight was measured using a Waters PL-GPC220 gel permeation chromatograph.
[0124] Membrane thickness: Use a thickness gauge with an accuracy of 0.1μm to perform thickness testing in accordance with Section 4 of GB / T 20042.3-2022 "Proton exchange membrane fuel cells Part 3: Proton exchange membrane test methods".
[0125] Tensile strength: Tested in accordance with GB / T 1040-2006 "Test method for tensile properties of plastics".
[0126] Proton conductivity: The impedance of the prepared proton exchange membrane was tested on an electrochemical workstation (Gamry Interface 5000E) using a two-electrode AC impedance method, with a test frequency of 1Hz to 1MHz. The conductivity test was carried out in a dry test chamber, with a controlled humidity of 30% RH and temperatures of 80°C and 100°C. The sample was first stabilized at this temperature and humidity for 30 minutes before the impedance test was carried out. Proton conductivity was calculated according to the following formula: Where σ is the proton conductivity (S / cm), L is the distance between the two electrodes (cm), R is the impedance test value (Ω), and S is the cross-sectional area of the proton membrane (cm 2 ).
[0127] Table 1
[0128]
[0129] It can be seen from the above that, compared with the comparative example, each embodiment of the present invention introduces a nitrogen heterocyclic structure into the side chain of the sulfonated polyaryletherketonesulfone, and performs phosphoric acid doping, so that the proton exchange membrane can maintain its proton conduction ability under high temperature and anhydrous conditions by means of the self-ionization characteristics of phosphoric acid, thereby realizing the high-temperature working scenario of the fuel cell. Moreover, the acid-base interaction between heterocyclic nitrogen and phosphoric acid is beneficial to slowing down the loss of phosphoric acid when the fuel cell is running at high temperature, thereby increasing the service life of the proton exchange membrane. The proton exchange membrane of the present invention can overcome the operating temperature limit of no more than 90°C of the perfluorosulfonic acid proton exchange membrane used in traditional fuel cells, and has the characteristics of high conductivity, high temperature resistance, and high durability.
[0130] In addition, it can be seen that when each process parameter is within the preferred range of the present invention, the overall effect is better.
[0131] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A proton exchange membrane, characterized in that: The proton exchange membrane is doped with phosphoric acid, and the membrane material includes a sulfonated polyaryletherketonesulfone containing a nitrogen heterocyclic side chain, and the sulfonated polyaryletherketonesulfone containing a nitrogen heterocyclic side chain has a structure shown in general formula (I): The number average molecular weight of the sulfonated polyaryletherketonesulfone containing a nitrogen-containing heterocyclic side chain is 10,000 to 300,000, 0% < x < 100%, 0% < y < 100%, 0% ≤ z < 100%, and x + y + z = 100%; R has the structure shown in general formula (II): Wherein, R1 is selected from imidazolyl or pyrazolyl, R2 is a C1-C4 branched or branched alkyl, and a is 1 or 2; Ar0 is a first non-sulfonated aromatic monomer, Ar1 is a sulfonated aromatic monomer, and Ar2 is a second non-sulfonated aromatic monomer.
2. The proton exchange membrane according to claim 1, characterized in that Ar0 has a structure shown in general formula (III): Wherein, A is selected from a vacant bond, O, a carbonyl group, or phenylene; and / or Ar1 has a structure shown in general formula (IV): Wherein, B is selected from a vacant bond, O, a carbonyl group, or phenylene; and / or Ar2 has the structure shown in general formula (V): Wherein, C is selected from a vacant bond, O, a carbonyl group or 3. The proton exchange membrane according to claim 1 or 2, characterized in that: R has any of the following structures:
4. The proton exchange membrane according to any one of claims 1 to 3, characterized in that The sulfonated polyaryletherketonesulfone containing a nitrogen-containing heterocyclic side chain has any one of the following structures: The number average molecular weight of the sulfonated polyaryletherketonesulfone with nitrogen-containing heterocyclic side chain is 18000-23000, 0%<x<100%, 0%<y<100%, 0%≤z<100%, and x+y+z=100%.
5. The proton exchange membrane according to any one of claims 1 to 4, characterized in that The doping amount of phosphoric acid in the proton exchange membrane is 10 to 50% by weight; and / or The thickness of the proton exchange membrane is 10-100 μm.
6. The method for preparing a proton exchange membrane according to any one of claims 1 to 5, characterized in that: The following steps are involved: Step S1, sequentially adding a nitrogen heterocyclic monomer raw material, a sulfonated aromatic hydrocarbon monomer raw material, a first non-sulfonated aromatic hydrocarbon monomer raw material and a second non-sulfonated aromatic hydrocarbon monomer raw material into a reaction container to obtain a mixed raw material, and then adding potassium carbonate, an organic solvent and toluene to obtain a raw material solution; Step S2, heating the raw material solution under nitrogen protection to obtain a polymerization system solution; Step S3, adding the polymerization system solution into a precipitant to precipitate a polymer to obtain a sulfonated polyaryletherketonesulfone having a nitrogen heterocyclic side chain; Step S4, dissolving the sulfonated polyaryletherketonesulfone having a nitrogen-containing heterocyclic side chain in dimethyl sulfoxide, and preparing a thin film by casting, spraying or spin coating; Step S5, soaking the film in an ethanol solution of phosphoric acid and drying it to obtain the proton exchange membrane.
7. The preparation method according to claim 6, characterized in that: The molar ratio of the nitrogen heterocyclic monomer raw material, the sulfonated aromatic hydrocarbon monomer raw material, the second non-sulfonated aromatic hydrocarbon monomer raw material and the first non-sulfonated aromatic hydrocarbon monomer raw material is (1-2):1:(0-1):3; and / or The nitrogen heterocyclic monomer raw material includes one or more of the following substances: 2,3,5,6-tetrafluoroterephthalene [(3-pyrazole) benzoyl], 2,3,5,6-tetrafluoroterephthalene [(3-imidazole) benzoyl], 2,3,5,6-tetrafluoroterephthalene [(3-methyl-5-imidazole) benzoyl], 2,3,5,6-tetrafluoroterephthalene [(4-methyl-5-imidazole) benzoyl]; and / or The sulfonated aromatic monomer raw material includes one or more of the following substances: 3,3'-disulfonic acid-4,4'-difluorobenzophenone disodium salt, 3,3'-disulfonic acid-4,4'-difluorodiphenyl sulfone disodium salt; and / or The first non-sulfonated aromatic monomer raw material includes one or more of the following substances: 4,4'-dihydroxybiphenyl, 4,4'-dihydroxydiphenyl ether, 4,4'-dihydroxybenzophenone, 4,4'-dihydroxydiphenyl sulfone, bisphenol A, bisphenol AF; and / or The second non-sulfonated aromatic hydrocarbon monomer raw material includes one or more of the following substances: 4,4'-difluorobiphenyl, 4,4'-difluorodiphenyl ether, 4,4'-difluorobenzophenone, and 4,4'-difluorodiphenyl sulfone.
8. The preparation method according to claim 6 or 7, characterized in that: The molar ratio of the mixed raw material to the potassium carbonate is 1:(1.0-1.1); and / or The organic solvent comprises N,N-dimethylacetamide and / or N-methylpyrrolidone; and / or In the raw material solution, the mass concentration of the mixed raw materials is 8-35%.
9. The preparation method according to any one of claims 6 to 8, characterized in that: The heating comprises a first heating and a second heating performed sequentially, wherein the first heating is performed at a temperature of 110 to 130° C. for 5 to 7 hours, and the second heating is performed at a temperature of 150 to 170° C. for 28 to 32 hours; and / or The precipitant is an aqueous solution of acetic acid with a mass concentration of 40 to 80%; and / or The mass concentration of the phosphoric acid ethanol solution is 40-80%; and / or The soaking temperature is 40-80° C. and the soaking time is 24-48 hours.
10. A fuel cell, characterized in that: The method comprises the proton exchange membrane according to any one of claims 1 to 4.
Citation Information
Patent Citations
High-temperature polyimide proton exchange membrane and preparation method thereof
CN103694490A
A high-temperature proton exchange membrane and its preparation method
CN108649257B
Cited By
Novel nano composite membrane with acid-doped pyridine side chain
CN121709651A